Bi-allelic mutations in MYL1 cause a severe congenital myopathy - Ravenscroft, Gianina (Hum Mol Genet, 2018)
Congenital myopathies are typically characterised by early onset hypotonia, weakness and hallmark features on biopsy. Despite the rapid pace of gene discovery, ∼50% of patients with a congenital myopathy remain without a genetic diagnosis following screening of known disease genes. We performed exome sequencing on two consanguineous probands diagnosed with a congenital myopathy and muscle biopsy showing selective atrophy/hypotrophy or absence of type II myofibres. We identified variants in the gene (MYL1) encoding the skeletal muscle fast-twitch specific myosin essential light chain (ELC) in both probands. A homozygous essential splice acceptor variant (c.479-2A > G, predicted to result in skipping of exon 5 was identified in Proband 1, and a homozygous missense substitution (c.488T>G, p.(Met163Arg)) was identified in Proband 2. Protein modelling of the p.(Met163Arg) substitution predicted it might impede intermolecular interactions that facilitate binding to the IQ domain of myosin heavy chain, thus likely impacting on the structure and functioning of the myosin motor. MYL1 was markedly reduced in skeletal muscle from both probands, suggesting that the missense substitution likely results in an unstable protein. Knock down of myl1 in zebrafish resulted in abnormal morphology, disrupted muscle structure and impaired touch-evoked escape responses, thus confirming that skeletal muscle fast-twitch specific myosin ELC is critical for myofibre development and function. Our data implicate MYL1 as a crucial protein for adequate skeletal muscle function and that MYL1 deficiency is associated with severe congenital myopathy.